Seeking congruency in digital optimisation and constructability in fabric formed ice shells utilising bending active frames. (2018) - Coar, Lancelot; Cox, Michael S.; Adriaenssens, Sigrid M.
Fabric formed structures are widely used to produce structural forms through the use of a temporary rigid framing to support a flexible membrane as formwork. Recent research has sought to introduce flexible support systems for fabric formwork so that they may participate in the parametric behaviour of fabric, while providing useful constraints for design. In the project presented here, a bending active frame is used to create a fabric formed ice shell using this approach. A focus is placed on the use of ice as a temporary structural material that allows for the iterative accumulation of mass during construction, as well as an analogous material for speculating about the use of other more permanent liquid-to-solid materials (like concrete). This project presents novel construction methods seeking to establish a meaningful link between digital optimisation design techniques and the often incongruent realities that must be confronted to build such a structure.